2017
DOI: 10.1007/s10103-017-2238-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency treatment induces fibroblast growth factor 2 expression and subsequently promotes neocollagenesis and neoangiogenesis in the skin tissue

Abstract: Radiofrequency (RF) treatment appears to be involved in production of new collagen fibrils and the improvement of existing collagen structures; however, the molecular bases of the effect of non-invasive RF on the skin tissue have not been fully elucidated. This study reports the effects of RF associated or not with hydrolyzed collagen (HC) in the skin tissue. Wistar rats were randomly divided into four groups, according to the treatment received: control group (G1, n = 5), no treatment; subjects in group G2 (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…The fat cells shrinkage is believed to be due to accelerated cellular metabolism and hence the release of free fatty acids by the radiofrequency field, 15 and partially due to increased vascularization (discussed below) induced by both RF/ TPE energies. 12,13,19,24 Besides lipolysis, RF and targeted pressure energy are also known to induce neocollagenesis and neoangiogenesis. Meyer and co-authors reported that the application of RF leads to the increased dermal thickness and type I collagen in rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fat cells shrinkage is believed to be due to accelerated cellular metabolism and hence the release of free fatty acids by the radiofrequency field, 15 and partially due to increased vascularization (discussed below) induced by both RF/ TPE energies. 12,13,19,24 Besides lipolysis, RF and targeted pressure energy are also known to induce neocollagenesis and neoangiogenesis. Meyer and co-authors reported that the application of RF leads to the increased dermal thickness and type I collagen in rats.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the study also showed an increase in the expression of fibroblast growth factor 2 (FGF2), an important signaling protein involved in angiogenesis, and consecutively in the microvessel density. 13 TA B L E 1 Collagen and elastin fiber amount and thickness, dermis thickness, and adipocytes' area. Data expressed as the mean ± standard deviation (SD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of radiofrequency energy to treat skin aging is based on internal thermogenesis induced by applied energy, and it is conventionally considered a nonablative procedure as suggested by Reference 1. As a consequence of such increase in internal temperature, vasodilation and increasing microcirculation occurs, new collagen formation, and contraction of existing collagen fibers 2‐4 . The radial fractional radiofrequency, instead, can be considered ablative by some authors 5 who suggest that it induces coagulation of dermal tissue in columns having the same diameter of the pins of the handpiece, but tissue's parts between the pins remain intact.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research on treatment effects in the dermis, collagen fibers were evaluated and categorized using a scoring system. This system could only be used to show qualitative rather than quantitative improvement . With our method, collagen fiber density can be compared using continuous values and statistical analysis, enabling quantitative assessment of treatment effects.…”
Section: Discussionmentioning
confidence: 99%